2019
DOI: 10.1111/sms.13553
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and factors of concussion events for tacklers in collegiate rugby union

Abstract: The purpose of this study was to determine the factors related to the occurrence of concussion in rugby tacklers. Match video records showing tackles leading to concussion were used to identify injury-inciting events. Additionally, noninjury tackles by concussed tacklers (prior to concussion) and position-matched tacklers from the same matches were used as a control cohort. All tackles were coded according to the tackling characteristics. The odds ratio (OR) was reported by logistic regression. The results dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 22 publications
1
11
1
Order By: Relevance
“…Tackling with an incorrect head position increased the likelihood of tackler-related cervical injuries. This finding is in line with that of a previous study (Sobue et al, 2018;Suzuki et al, 2020). Tanabe et al analyzed the kinematic aspects of tackles with the incorrect head position in laboratory conditions (Tanabe et al, 2019).…”
Section: Contact Phasesupporting
confidence: 94%
“…Tackling with an incorrect head position increased the likelihood of tackler-related cervical injuries. This finding is in line with that of a previous study (Sobue et al, 2018;Suzuki et al, 2020). Tanabe et al analyzed the kinematic aspects of tackles with the incorrect head position in laboratory conditions (Tanabe et al, 2019).…”
Section: Contact Phasesupporting
confidence: 94%
“…the tackle 13 are related to the occurrence of tacklerrelated concussion. In the aspect of the ball-carrier, an accelerating ball-carrier 6 13 and evasive manoeuvre prior to tackle 8 have a relationship with the occurrence of tackler-related concussion. In addition, the latest systematic scoping review reported that 'head up and facing forward' and 'shortening steps' were associated with injury prevention and tackling performance in rugby union.…”
Section: What Are the New Findings?mentioning
confidence: 99%
“…Injury surveillance of a Japanese collegiate rugby union team was conducted between 2008 and 2015 with informed consent from the players. 8 There was no patient or public involvement.…”
Section: Concussion Datamentioning
confidence: 99%
See 2 more Smart Citations